Clinical utility of anti-interleukin 5 monoclonal therapy in asthma using a national, centralised, outcome-based system of drug access. Issue 1 (27th September 2022) - O'Leary, Caroline; Schultz, Christopher; Walsh, Cathal; Adams, Roisin; Casey, Deborah; Lane, Stephen; Harrison, Michael; Doyle, Shane; Costello, Richard W; King, Fionnuala; Murphy, Desmond M
Abstract : Introduction: Interleukin 5 (IL-5) inhibitors are an important therapeutic advance in the management of severe, refractory, eosinophilic asthma. However, their utilisation should be targeted to maximise their benefits. This study used multisite, centralised, national data collected over 18 months to perform an observational integrated, retrospective, cohort study of selection criteria for initiation and continuation of IL-5 inhibitor treatment in Ireland. Materials/patients and methods: We used data from 230 patients who were given anti-IL-5 monoclonal therapy (reslizumab, mepolizumab or benralizumab) in Ireland between 2018 and 2020. Reimbursement of these drugs in Ireland requires fulfilling eligibility criteria defined by the Acute Hospitals Drugs Management Programme with continued reimbursement requiring ongoing submission of clinical data demonstrating clinical effectiveness. Results: IL-5 inhibitor use for 18 months was associated with a total reduction in asthma-associated hospital admissions of 108 (p=0.036) and in non-hospital exacerbations of 85 in 18 months (p=0.014). Respiratory-associated GP visits were reduced from 637 in 12 months to 89 at 6 months and 210 at 18 months of treatment (p<0.001). Oral corticosteroid requirement was reduced or stopped entirely (p<0.001). Subgroup analysis of one site replicated these results and showed a significant reduction in the Asthma Control Questionnaire Score (p<0.001) Conclusions: Selected patients continued on IL-5 treatment to 18 months had significantly reduced exacerbations, GP visits, oral corticosteroid use and asthma-associated hospitalisations. These results show that anti-IL-5 therapy, in carefully selected and monitored patients with asthma, results in significant improvements in clinical outcomes in a real-world setting.